Liposomal mitoxantrone-based multidrug chemotherapy as a bridge to allogeneic hematopoietic stem cell transplantation in relapsed/refractory acute lymphoblastic leukemia (ALL) after immunotherapy failure: a case report - Deng, Jin; Chen, Hongxia; Yang, Yi; Ji, Hua; Liu, Hui (Frontiers in Medicine, 2024)
Acute lymphoblastic leukemia (ALL) represents a malignancy involving early-stage differentiated lymphoid cells that invade the bone marrow, blood, and extramedullary sites. First-line treatment spans 2–3 years with induction, consolidation, intensification, and long-term maintenance phases. Relapsed/refractory (R/R) ALL typically carries an adverse prognosis, and there is currently no standard of care for this disease. Here, we present a case of R/R ALL that responded effectively to liposomal mitoxantrone-based multidrug chemotherapy, resulting in a rapid complete response after 35 days of therapy. Subsequently, the patient was successfully treated with allo-HSCT. At 5 months follow-up, the patient was alive and leukemia-free. Additionally, no severe adverse events were recorded during liposomal mitoxantrone treatment or hospitalization for allo-HSCT. Given the encouraging efficacy and the manageable adverse events observed in our case, liposomal mitoxantrone-based multidrug chemotherapy should be further explored as a bridge to allo-HSCT in patients with R/R ALL.